Mobility of photosynthetic proteins - Kaňa, Radek (Photosynthesis research, 2013)
The mobility of photosynthetic proteins represents an important factor that affects light-energy conversion in photosynthesis. The specific feature of photosynthetic proteins mobility can be currently measured in vivo using advanced microscopic methods, such as fluorescence recovery after photobleaching which allows the direct observation of photosynthetic proteins mobility on a single cell level. The heterogeneous organization of thylakoid membrane proteins results in heterogeneity in protein mobility. The thylakoid membrane contains both, protein-crowded compartments with immobile proteins and fluid areas (less crowded by proteins), allowing restricted diffusion of proteins. This heterogeneity represents an optimal balance as protein crowding is necessary for efficient light-energy conversion, and protein mobility plays an important role in the regulation of photosynthesis. The mobility is required for an optimal light-harvesting process (e.g., during state transitions), and also for transport of proteins during their synthesis or repair. Protein crowding is then a key limiting factor of thylakoid membrane protein mobility; the less thylakoid membranes are crowded by proteins, the higher protein mobility is observed. Mobility of photosynthetic proteins outside the thylakoid membrane (lumen and stroma/cytosol) is less understood. Cyanobacterial phycobilisomes attached to the stromal side of the thylakoid can move relatively fast. Therefore, it seems that stroma with their active enzymes of the Calvin-Benson cycle, are a more fluid compartment in comparison to the rather rigid thylakoid lumen. In conclusion, photosynthetic protein diffusion is generally slower in comparison to similarly sized proteins from other eukaryotic membranes or organelles. Mobility of photosynthetic proteins resembles restricted protein diffusion in bacteria, and has been rationalized by high protein crowding similar to that of thylakoids.
Keywords: difuze; transport proteinů; tylakoidy; Phycobilisomes; Photosynthesis; Plant Proteins; Diffusion; fotosyntéza; rostlinné proteiny; Thylakoids; fykobilizomy; Protein Transport